1985
DOI: 10.1002/j.1460-2075.1985.tb03686.x
|View full text |Cite
|
Sign up to set email alerts
|

Precise epitope mapping of the murine transformation-associated protein, p53.

Abstract: Murine p53 cDNA sequences were cloned into an in vitro expression vector, Protem Hind. Four deletion libraries were generated using Bal31 double‐stranded exonuclease; two being made from constructs encoding a fusion protein constructed from SV40 small t sequences and the p53 clone, p27.la; and two from the full length p53 clone, pp53‐5. Both 5′‐ and 3′‐terminal deletions of the p53 gene were made. Transcription of these constructs using Escherichia coli RNA polymerase holoenzyme, followed by translation in mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

1985
1985
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 28 publications
5
78
0
Order By: Relevance
“…Conformation-specific monoclonal antibodies can be used to analyze the structure of p53, and a number of antibodies recognizing a specific region of the protein associated with functional properties of p53 have been raised. By binding to the C terminus (amino acids 372-381), the antibody PAb421 can allosterically activate latent p53 for DNA binding (Wade-Evans and Jenkins, 1985;Hupp et al, 1992Hupp et al, , 1994. DO-1 binds to the highly antigenic N terminus (amino acids 20 -25) of p53 (Stephen et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Conformation-specific monoclonal antibodies can be used to analyze the structure of p53, and a number of antibodies recognizing a specific region of the protein associated with functional properties of p53 have been raised. By binding to the C terminus (amino acids 372-381), the antibody PAb421 can allosterically activate latent p53 for DNA binding (Wade-Evans and Jenkins, 1985;Hupp et al, 1992Hupp et al, , 1994. DO-1 binds to the highly antigenic N terminus (amino acids 20 -25) of p53 (Stephen et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of monoclonal antibodies produced against human p53 demonstrated a strong bias in the epitope recognised by these monoclonal antibodies. Most of them recognised epitopes localised in the amino terminus of p53 (Wade-Evans & Jenkins, 1985;Vojtesek et al, 1992;Bartek et al, 1993;Legros et al, 1993). Furthermore, we showed that p53 antibodies in sera of animals hyperimmunised with human p53 recognised epitopes similar to those identified in a previous work (Schlichtholz et al, 1992; Y. Legros & T. Soussi, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots containing equal amounts of TCA-insoluble radioactivity were first precleared, incubated with anti-P53 monoclonal antibodies or a control MAb, MOPC2 1, and then immunoprecipitated using protein ASepharose, which was followed by SDS-polyacrylamide gel electrophoresis on a 10% gel essentially as described (15). Anti-p53 monoclonal antibodies used were PAb 1801 (Oncogene Science, Manhasset, NY) (16) (16,18).…”
Section: Methodsmentioning
confidence: 99%